THE SYRIAN CONFLICT AND TURKEY'S HUMANITARIAN RESPONSE - Oztig, Lacin Idil (TURKISH POLICY QUARTERLY, 2016)
Turkey has followed an open-door policy towards the Syrian refugees since the start of the conflict in Syria in 2011. With the intensification of violence, Syria has now replaced Afghanistan as the state that generates the most refugees in the world. Currently, Turkey hosts more than 2.7 million refugees. In this paper, an analysis of Turkey's response to the refugee crisis is presented, by shedding light on the living and working conditions of Syrian refugees. The second part of the article looks at Turkey's border policy and its humanitarian policies in response to this crisis.
Keywords: Government & Law